2018
DOI: 10.1111/jpy.12759
|View full text |Cite
|
Sign up to set email alerts
|

Thermal niche evolution of functional traits in a tropical marine phototroph

Abstract: Land-based plants and ocean-dwelling microbial phototrophs known as phytoplankton, are together responsible for almost all global primary production. Habitat warming associated with anthropogenic climate change has detrimentally impacted marine primary production, with the effects observed on regional and global scales. In contrast to slower-growing higher plants, there is considerable potential for phytoplankton to evolve rapidly with changing environmental conditions. The energetic constraints associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 64 publications
4
18
1
Order By: Relevance
“…Natural genetic diversity of phytoplankton populations can alleviate the effect of N limitation if better adapted genotypes to both stressors (warming and nutrient limitation) are present in the population. However, the results of the present work and others (Baker et al ) suggest that trade‐offs between adaptation to high temperatures and resource limitation may be general, constraining the response to selection in phytoplankton. Declines in species richness may lead to decreased productivity (Cermeño et al ).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Natural genetic diversity of phytoplankton populations can alleviate the effect of N limitation if better adapted genotypes to both stressors (warming and nutrient limitation) are present in the population. However, the results of the present work and others (Baker et al ) suggest that trade‐offs between adaptation to high temperatures and resource limitation may be general, constraining the response to selection in phytoplankton. Declines in species richness may lead to decreased productivity (Cermeño et al ).…”
Section: Discussioncontrasting
confidence: 49%
“…Recent laboratory experiments document fast thermal adaptation: within several hundred generations, the optimum temperature for growth and niche width increased in phytoplankton grown above their thermal optimum (Listmann et al 2016;O'Donnell et al 2018). However, little is known about how other stressors affect thermal adaptation (Boyd & Hutchins 2012;Boyd et al 2015;Baker et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, experimental evolution is the study of evolutionary processes occurring in experimental populations in response to the conditions imposed upon them (Kawecki et al., 2012). A small number of temperature selection experiments have been carried out in various species of microalgae (Baker et al., 2018; Flores‐Moya, Costas, & López‐Rodas, 2008; Flores‐Moya et al., 2012; Hinners, Kremp, & Hense, 2017; Jin, Gao, & Beardall, 2013; Listmann, LeRoch, Schlüter, Thomas, & Reusch, 2016; O’Donnell, Hamman, Johnson, Klausmeier, & Litchman, 2017; Padfield, Yvon‐Durocher, Buckling, Jennings, & Yvon‐Durocher, 2016; Schaum, Buckling, Smirnoff, Studholme, & Yvon‐Durocher, 2018; Schaum & Collins, 2014; Schlüter et al., 2014), and three studies to date have shown rapid adaptation in Symbiodiniaceae to elevated temperatures using experimental evolution (Chakravarti et al., 2017; Chakravarti & van Oppen, 2018; Huertas, Rouco, Lopez‐Rodas, & Costas, 2011). First, two unknown species of the Symbiodiniaceae were able to grow at 30°C with similar rates to the wild‐type populations at ambient temperature after only ~70 generations of laboratory selection (Huertas et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation present within algal species has remained largely unstudied as a source that may fuel such adaptation (Buerger et al 2020;Parkinson, Banaszak, Altman, LaJeunesse, & Baums 2015a). The potential for genetic variation within algal species to fuel adaptation to changing conditions can be assessed in the laboratory via experimental evolution experiments where algal strains are selected over several generations under heat stress conditions (Baker et al 2018;Buerger et al 2020;Chakravarti & van Oppen 2018). In one instance, Symbiodiniaceae strains adapted to heat stress selection in vitro but once introduced into the coral partner, gains were not always retained highlighting the complexity of adaptation in the context of mutualistic partners (Buerger et al 2020).…”
mentioning
confidence: 99%